Efeitos comportamentais, neuroquímicos e bioquímicos do etanol em roedores, na presença e na ausência de antagonistas dopaminergico, glutamatergico e opioide - Vasconcelos, Silvânia Maria Mendes (2001)
In the present work, behavioral, neurochemical (determination of monoamines and metabolites, as well as, aminoacids leveis in striatum) and biochemical (glucose, transaminases, lipoproteins and apoproteins) alterations produced by ethanol alone and in association with glutamatergic, dopaminergic and opioid antagonists were studied. Male Wistar rats (150-230 g) and Swiss mice (28-34 g) in two experimental protocols were used (Pl= ketamine, haloperidol or naltrexone administraiion to ethanol pre- treated animais; P2= Association of ethanol and antagonist). The results demonstrated that the spontaneous locomotor activity (SLA) was decreased only after ethanol adminstration at high doses. There was a tendency to decrease SLA in the association of ketamine + ethanol after 30 min and 48 h withdrawal. Haloperidol decreased SLA only 30 min after administration, this effect was reverted 48 h after drug withdrawal, and was not alterated in the presence of ethanol. Naltrexone tended to decrease SLA after 48 h, this effect was not influenced by ethanol, which alone, at high doses induced motor incoordination in mice in the first days of treatment. The acute and subchronic treatment with ethanol at high doses caused an increase in dopamine (DA) and 3,4- dihydroxyphenylacetic (DOPAC) leveis. However, an inverse effect was observed after 30 days treatment. Leveis of norepinephrine (NE), 5-hydroxytryptamine (5-HT) and 5- dihydroxyindolacet (5-HIAA) were also altered in the presence of ethanol and this effect was dependent on the dose, time of administration and time of withdrawal. Ketamine, haloperidol or naltrexone alone or in association with ethanol also interfered with DA, DOPAC, homovanillic acid (HVA), NE, 5-HT and 5-HIAA leveis, suggesting that these drugs may act directly in these systems or, indirectly, through a modulation process. Ethanol, after acute and subchronic administration, in high doses, caused a downregulation of Dl- and D2-like receptors. Kd values for Dl and D2-like receptors were decreased only in the acute treatment after 48 h withdrawal. In animais treated with haloperidol or naltrexone, and previously exposed to ethanol. In these two protocols a decrease in Kd value was observed only after administration of ketamine, haloperidol or naltrexone. Ethanol also increased glutamate leveis, indicating a modulatory effect in the release of this aminoacid. Ketamine, haloperidol and naltrexone alone, or in association with ethanol, caused alterations mainly in the leveis of aspartate and glutamate which were dependent to the protocol used. In the biochemical study, chronic administration of ethanol induced an increase in the concentration of enzymes related to hepatic fiinction, triglycerides (TGI), High Density Lipoprotein (HDL) and total cholesterol (T- CHOLE) leveis, without alterations in the apolipoproteins (APO Al) leveis. The treatment with ethanol + ketamine increased APO B leveis. Haloperidol alone showed a cardioprotector effect evidenciated by the increase of APO Al and decrease of APO B and T-CHOLE leveis. However, this effect decreased with previous exposure to ethanol (detected by an increase in TGI), and disappeared in the association of haloperidol with ethanol (detected by the increase of TGI and T-CHOLE and the absence of effect on APO Al). Naltrexone alone presented a cardioprotector effect evidenciated by an increase in APO Al and decrease of APO B and T-CHOLE leveis. This effect was also observed after previous exposure to ethanol, increase of APO Al and decrease of T-CHOLE leveis, and in the association of naltrexone with ethanol, showed by a decrease of APO B, TGI and T-CHOLE leveis. The results in the present work showed that ethanol interferes with many neurotransmitters and that glutamatergic, dopaminergic and opioid antagonists interfere with ethanofs effects in rat striatum.